Analisis Pengaruh Implementasi Aplikasi KAI Access Terhadap Kepuasan Pengguna Layanan PT. Kereta Api Indonesia Di Kota Semarang - Agus Bahrudin (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
KAI access is the official application from KAI for making orders, as a means of boarding passes, train tickets. This application was created to make it easier, especially for KAI passengers, to order tickets, as a medium for finding route information and train schedules according to what train passengers need. Implementation of KAI Access is measured from four indicators including communication, resources, disposition and bureaucratic structure. Meanwhile, the level of satisfaction of PT service users. KAI is seen from 9 indicators including requirements, systems, mechanisms and procedures, costs/tariffs, product specifications, types of services, competency of implementers, behavior of implementers, handling complaints, suggestions and input, and facilities and infrastructure.The results of the research show that the cumulative score for KAI Access Implementation obtained a percentage of 84.29, which is in the high category, while the cumulative score for the level of satisfaction of PT service users. KAI obtained a percentage of 82.79, including the high category. The results of statistical calculations through the product moment correlation test obtained r_count > r_tabel (0.931 > 0.279) at a significance level of 5% with N-50, which means there is a positive influence of the implementation of KAI Access on the level of satisfaction of PT service users. KAI in Semarang City